Translation and bilingual dictionaries - Chan, Sin-wai (Lexicographica. Series maior, 2004)
Is the bilingual dictionary really the translator's best friend? Or is it the case that all translators hate all dictionaries? The truth probably lies half-way. It is difficult to verify anyway, as the literature on the subject(s) is limited, not helped by the fact that Lexicography and Translation have stood apart for decades despite their commonality of purpose. Here is a volume, based on the proceedings of a successful conference at Hong Kong, that may at last provide some answers.